(untitled) (mathematica didactica, 2005)
Solving extreme value problems belongs into the calculus classroom, and rightly so, since the criteria of curve sketching place an efficient solution algorithm at our disposal. Now and then, however, one is left with the impression that this topic is virtually bound tobe tied to these calculus procedures. Relativising this very narrow view is a first step in broadening the scope of the topic. The article presents the opportunities that arise from sucha change in attitude and thus allow for an understanding treatment of this subject.